Degree of extraversion and physiological responses to physical pain and sadness. Issue 5 (21st July 2014) - Park, Mi‐Sook; Lee, Kyung Hwa; Sohn, Sunju; Eom, Jin‐Sup; Sohn, Jin‐Hun
<x xml:space="preserve">Abstract</x> Extraversion is a personality frequently discussed as one of the strongest and most consistent factors that relates to individual subjective wellbeing. The goal of this study was to better understand how people with varying degrees of extraversion psychologically and physiologically respond differently to unpleasant circumstances. Emotional responses (e.g., levels of intensity, valence, and arousal) were assessed in determining the sensitivity level to negative stimuli that were specifically designed to provoke physical pain and sadness emotion. Physiological changes (e.g., heart rate (HR), blood volume pulse (BVP), and respiratory sinus arrhythmia (RSA)) were also measured during pain and sadness to observe sympathetic and parasympathetic activities. Our results showed that the degree of extraversion was associated with less unpleasant responses to sadness, less HR responses to both pain and sadness, and greater RSA responses to sadness. The findings suggest that the lower HR reactivity to painful and sad situations and greater RSA reactivity to sad situations in extraversion could be possibly due to increased parasympathetic activity. Additionally, enhanced parasympathetic activity to negative situations may explain an important mechanism underlying the positive connection between extraversion and subjective wellbeing.